Human Resource Management: A Study on Private University in Indonesia - Zahera Mega Utama (STAI Hubbulwathan Duri, 2023)
This paper aims to chronicle the historical development of Human Resource Management (HRM) as both an established academic field and a professional enterprise. The study adopts a desk-based methodology to examine the literature that has played a pivotal role in comprehending the beginnings, evolution, and professional advancement of HRM. A total of ten publications, sourced from scholarly journals, were selected to accurately depict the current situation. The papers underwent examination using three qualitative analysis procedures: data categorization, validation, and inference formulation. The study's findings indicated that mergers and acquisitions, talent management, succession planning, industrial and labour relations, and diversity and inclusion were previously the core components of human resources. The transition took place due to globalisation, corporate consolidation, technical progress, and more study. Academic institutions, professional bodies, and individual firms have devised specialised programmes of study to train future professionals for the specific obligations of the post. Multiple publications regarding human resources indicate that academic and practitioner organisations are also keen on making contributions to and advancing the sector.